catena-Poly[[tetraaqua[mu(2)-1,4-bis(1,2,4-triazol-1-yl)butane-kap pa N-2(4):N-4 `]cadmium(II)] sulfate] - Song, Jing-Jing; Zhang, Kou-Lin; Ng, S.W. (International Union of Crystallography, 2010)
In the polymeric title compound, {[Cd(C8H12N6)(H2O)(4)]SO4}(n), the Cd-II atom is located on an inversion center and coordinated by four water molecules and two 1,4-bis(1,2,4-triazol-yl)butane ligands in a distorted CdO4N2 octahedral geometry. The 1,4-bis(1,2,4-triazol-yl)butane ligand is centro-symmetric, the mid-point of the central C-C bond being located on an inversion center. It links adjacent water-coordinated metal atoms into polymeric chains running along the c axis. Adjacent chains are linked by O-H center dot center dot center dot N hydrogen bonds. The S atom of the sulfate anion is located on a twofold rotation axis, thus the sulfate anion is equally disordered over two sites. The sulfate anion links with the polymeric chains via O-H center dot center dot center dot O hydrogen bonds, generating a three-dimensional supramolecular network.